Interferon-λ4 (IFNL4) transcript expression in human liver tissue samples. - Ahmad Amanzada; Waltraut Kopp; Ulrich Spengler; Giuliano Ramadori; Sabine Mihm (PLoS ONE, 2013)
Eradication of hepatitis C virus (HCV) infection, both spontaneous and treatment-induced, is marked by the wildtype allele C of a single nucleotide polymorphism upstream of the IL28B gene, rs12979860. This favorable allele was recently described to be in linkage disequilibrium with the wildtype allele TT of a dinucleotide polymorphism, ss469415590, located within a new protein-coding gene. While the TT allele introduces a frame-shift and disrupts the open reading frame, only the variant allele, ΔG, creates a novel type III interferon (IFN) protein, IFN-λ4/IFNL4. Absence of IFNL4 is thus supposed to favor resolution of HCV infection. As to date IFNL4 mRNA transcription has only been investigated in polyI:C-stimulated primary human hepatocytes and not yet in HCV infection in vivo, this study analyzed IFNL4 mRNA expression in human liver biopsy specimens. Samples were obtained from patients with a broad panel of disorders including no liver disease, liver diseases of non-viral etiology, chronic hepatitis B and chronic hepatitis C. Hepatic IFNL4 transcripts were detectable exclusively in a subgroup of chronic hepatitis C patients (24/45). Their amounts were positively related to liver HCV RNA copy numbers (p = 0.0023, r = 0.56) suggesting that the hepatic viral load influences IFNL4 transcription irrespective of IFNL4 governing genotype. Both, the IFNL4 creating allele ΔG (p<0.0001) and actual IFNL4 transcription (p = 0.0015) were found to be correlated to the activation of IFN stimulatory genes (ISGs). By contrast, IFNL4 ss469415590 genotypes were not found to be related to IFN-λ2/3/IL28 or IFN-λ1/IL29 gene expression. In conclusion, this study is the first report on intrahepatic transcript levels of the recently discovered IFNL4 gene. Data indicate that HCV infection in particular might activate IFNL4 transcription in the liver. It provides a possible explanation as to why hepatitis C patients show ISG stimulation in their livers in the apparent absence of an induction of other IFN subtypes.